Chest Tube Drainage, Bone Radiotherapy, and Brain Radiotherapy in Advanced Lung Cancer: A Retrospective Analysis of Associated Factors and Survival - Shoko Sonobe Shimamura; Takehito Shukuya; Kazuhisa Takahashi; Yasushi Shintani; Ikuo Sekine; Koichi Takayama; Akira Inoue; Isamu Okamoto; Tomoya Kawaguchi; Nobuyuki Yamamoto; Etsuo Miyaoka; Ichiro Yoshino; et al. (Thoracic Cancer)
ABSTRACT Background Palliative interventions, such as chest tube drainage and radiotherapy for bone and brain metastases, are crucial for managing survival and quality of life in patients with advanced lung cancer. Methods This retrospective study analyzed 8171 patients with unresectable Stage IV lung cancer from the Japanese Joint Committee of Lung Cancer Registry (JJCLCR) database. At treatment initiation, 8.6% of patients underwent chest tube drainage, 9.9% underwent bone radiotherapy, and 11.5% underwent brain radiotherapy. In this study, associated factors for palliative interventions were evaluated, and their impact on patient survival was also assessed. Results High‐associated factors for upfront chest tube drainage included age ≥ 75 years, ECOG‐PS ≥ 2, pleural nodules, and adenocarcinoma, while EGFR mutation, serum albumin ≥ 3.2 mg/dL, adrenal gland, and brain metastases were low‐associated factors. For upfront brain radiotherapy, low‐associated factors included malignant pleural effusion (MPE) and bone metastases, whereas ECOG‐PS ≥ 2 was a high‐associated factor. High‐associated factors for upfront bone radiotherapy were serum albumin ≥ 3.2 mg/dL, ECOG‐PS ≥ 2, adenocarcinoma, and squamous cell carcinoma, while pleural nodules, MPE, liver, and brain metastasis were low‐associated factors. Patients receiving upfront bone radiotherapy had shorter survival, whereas survival did not significantly differ for those with or without upfront chest tube drainage or brain radiotherapy. Conclusion This study identified associated factors for palliative interventions in advanced lung cancer and their association with overall survival. Future prospective studies with more detailed data are necessary to confirm these findings and improve clinical decision‐making. Trial Registration: Approval No. 15,321